Respuesta :

MN=6cm

NP= 4 cm

Step-by-step explanation:

Step 1:

By the property of symmetry in triangle

[tex]\frac{BA}{BC} =\frac{MN}{NP}[/tex]

By applying componendo and dividendo rule above equation is modified as

[tex]\frac{BA+BC}{BA-BC} = \frac{MN+NP}{MN-NP}[/tex]

Step 2:

Applying the values in above equation

[tex]\frac{12+8}{12-8} =\frac{10}{MN-NP}[/tex]

on simplification

MN-NP= [tex]\frac{10*4}{20}[/tex]

MN-NP=2

MN+NP=10

on solving above equations

2[tex]*[/tex]MN=12

MN=6 cm

NP=10-MN

    =10-6

    =4 cm

Ver imagen bhuvna789456
ACCESS MORE